The international responsibility of States due to cancel or not to recognize awards - Cantuarias Salaverry, Fernando (2014)
In the framework of international treaties, with special emphasis on theBilateral investment treaty (Bit), various responsibilities for states that comprise arise. However , what happens when the courts of a country interfere contrary to international standards in full force and effect of an award, the impact caused in that state and that leading to be internationally liable to a Bit or FtA are studied in this essay. the author further analyze jurisprudence of investment arbitration tribunals in cases Saipem v. Bangladesh, ATA v. Jordan Frontier Petroleum v. Czech Republic and White Industries v. India, also focuses on the case of Peru; and urges members of a treaty respect the rules of the game.